Control de inventario y su influencia en la rentabilidad de la empresa "Mega Ferretería Bonilla" del cantón La Maná, Provincia de Cotopaxi, año 2021 - Albán Conrado, Manoly Sayonara (2022)
The present work entitled inventory control and its influence on the profitability of the company Mega Ferretería Bonilla" of La Maná canton aims to evaluate and determine the effect of inventory on the profitability of the Mega Ferretería Bonilla, theoretically based on concepts such as stock, productivity and the management in the purchase and sale of inventories within the hardware store. The methodology used encompasses a descriptive and field approach because it is necessary to describe the procedures currently being carried out in inventory management within the hardware store. So that, the shortcomings that have occurred in the procedures can be identified due to poor management and control of inventories that can cause repercussions on the profitability decrease, based on the obtained results it can be verified that the company handles a Morpheus control and sale system, which allowed empirically know the stock of merchandise and at the same time evidence the shortcomings that exist within the inventory control procedure, such as the loss and damage of merchandise, based on these results there was a need to implement a manual of policies and procedures for inventory control for the Bonilla Mega Hardware store, with the only objective to establish policies and procedures in the inventory area for an adequate administration and simultaneously improve the management of purchase-sale processes by avoiding risks and facilitating decision-making.